(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Societal foundations to environmental sustainability, areas of human-environment interface and resource management effectiveness have great significance in sustainable development parameters. Accordingly, the discourses of this research paper include the views of natural and social scientists, tools and languages used in environmental sustainable parlance for assessing on multidisciplinary types of work undertaken as of now. Environmental sustainability is concerned with bio-ecological sciences needs integrative framework, human-environment interface for effective utilization of resources to peace, progress and prosperity of mankind. Developmental activities need strategic way of dealing with the things to control the man-made elements through judicious monitoring as well as sequential simulation of the environmental issues with time bound scientific plans, realistic programs, and appropriate targets. All these are illuminated in sparkling manner to cope up with the man-made causes of environmental degradation for healthy human living tendencies and protection of our future generations. The study provides important findings on different evidential reviews to understand the global changes and to meet the challenges of time with scientific visions, adequate policy formulations by the national governments. Also, some measures are suggested for sustainable development and mitigating environmental problems. At the end, adequate recommendations are given for scientific developmental goals in terms of utilizing the earth’s resources as an urgent need. It further provides guidelines on the basis of empirical research evidences to alarming changes in global environment, and concludes on making appropriate decisions for harmonious development with nurturing environmental resources for better future, prospective growth of human civilization and peaceful social progress to achieve sustainable development goals (SDGs).